Impact of playing video game towards cognitive control and reaction times / Muhammad Ariff Munshir Mohd Pozi ... [et al.]. - Mohd Pozi, Muhammad Ariff Munshir; Mohd Zaid, Amelia Natasya; Zianuddin, Muhammad Haiqal; Mohd Nizam, Muhammad Hariz; Zani, Muhammad Isamuddin; Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study examines the impact of extensive video game playing on cognitive control and visuomotor performance. By analyzing reaction times and accuracy, it sheds light on the differences between video game players (VGPs) and non-video game players (non-VGPs), thus addressing gaps in understanding Simon-task performance and its implications for visuomotor and cognitive abilities [1]. A causal-comparative design was employed to analyze cognitive control and visuomotor performance in male participants (n = 30, 18–25 years) with normal vision and right-handedness. Using tools within Psytoolkit (PsychologyJobs.com), tests such as the Simon-task and Aim Trainer were utilized to assess reaction times and accuracy. Participants were grouped into VGPs (n = 15, 3+ days/week gaming) and NVGPs (n = 15, minimal gaming), matched for demographics, and tested under controlled conditions. Data was analyzed using the Mann-Whitney U Test with statistical significance set at (p<0.05) to seek any possible differences between groups.